2023
DOI: 10.3310/xqwu4117
|View full text |Cite
|
Sign up to set email alerts
|

Early evaluation of the Children and Young People’s Mental Health Trailblazer programme: a rapid mixed-methods study

Abstract: Background The Children and Young People’s Mental Health Trailblazer programme is funding the creation of new mental health support teams to work in schools and further education colleges. Mental health support teams directly support children and young people with ‘mild to moderate’ mental health problems and work with school and college staff to promote well-being for all. A new workforce of education mental health practitioners is being trained for the teams. Objective(s) The National Institute for Health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Part of the Transforming Children and Young People's Mental Health Green Paper (Department for Education, 2017), MHSTs are now working in 4,700 schools and colleges across England to improve early intervention and access to support (NHS England, 2022). An initial evaluation of the first "Trailblazer" sites found positive reports of improved partnership working between schools and the NHS, as well as positive feedback from children and young people who had been supported (Ellins et al, 2021). Staff in some sites also reported feeling more comfortable talking to pupils about mental health issues and noted a more proactive and positive culture around wellbeing in their setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the Transforming Children and Young People's Mental Health Green Paper (Department for Education, 2017), MHSTs are now working in 4,700 schools and colleges across England to improve early intervention and access to support (NHS England, 2022). An initial evaluation of the first "Trailblazer" sites found positive reports of improved partnership working between schools and the NHS, as well as positive feedback from children and young people who had been supported (Ellins et al, 2021). Staff in some sites also reported feeling more comfortable talking to pupils about mental health issues and noted a more proactive and positive culture around wellbeing in their setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, some educational settings struggled to engage, and school staff reported that pupils were still falling between gaps in services and struggling to access the right support. Additionally, capacity and staff retention in MHSTs were widely reported as challenges, with many issues around workforce stability (Ellins et al, 2021).…”
Section: Discussionmentioning
confidence: 99%